2018
DOI: 10.5194/acp-18-17047-2018
|View full text |Cite
|
Sign up to set email alerts
|

The relative impact of cloud condensation nuclei and ice nucleating particle concentrations on phase partitioning in Arctic mixed-phase stratocumulus clouds

Abstract: Abstract. This study investigates the interactions between cloud dynamics and aerosols in idealized large-eddy simulations (LES) of Arctic mixed-phase stratocumulus clouds (AMPS) observed at Oliktok Point, Alaska, in April 2015. This case was chosen because it allows the cloud to form in response to radiative cooling starting from a cloud-free state, rather than requiring the cloud ice and liquid to adjust to an initial cloudy state. Sensitivity studies are used to identify whether there are buffering feedback… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 39 publications
(48 reference statements)
13
56
1
Order By: Relevance
“…In agreement with previous findings (e.g. by Possner et al, 2017; Solomon et al, 2018; Stevens et al, 2018), the LWP (and IWP) of the mixed‐phase cloud increased with increasing CCN concentration. However, the change was non‐linear so that a CCN increase at low levels gave a smaller impact on the LWP than a change at high CCN levels.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with previous findings (e.g. by Possner et al, 2017; Solomon et al, 2018; Stevens et al, 2018), the LWP (and IWP) of the mixed‐phase cloud increased with increasing CCN concentration. However, the change was non‐linear so that a CCN increase at low levels gave a smaller impact on the LWP than a change at high CCN levels.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with Possner et al (2017), Stevens et al (2018) and Solomon et al (2018), we also found that a doubling of the ICNC decreases the LWP (Figure 11). The higher ICNC pushed the cloud into a tenuous regime and the surface temperature decreased rapidly.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For example, Coopman, Garrett, et al () using multiyear satellite, meteorological, and tracer transport model data found that low‐level Arctic cloud response to anthropogenic aerosols are 2 to 8 times higher than in lower latitudes and that the role of biomass aerosols to Arctic clouds response have been overstated in previous studies. Consequently, the relative contribution of aerosol to the radiative forcing of Arctic clouds is still highly uncertain (Coopman, Riedi, et al, ; Flanner, ; Garrett et al, ; Garrett et al, ; Norgren et al, ; Solomon et al, ; Wylie & Hudson, ; Zamora et al, ; Zhao & Garrett, ).…”
Section: Introductionmentioning
confidence: 99%